THE INFLUENCE OF PARTICIPATION LEADERSHIP, ORGANIZATIONAL CULTURE, INNOVATION TO ORGANIZATIONAL CAPABILITY AND COOPERATIVE PERFORMANCE IN THE PROVINCE OF SOUTH KALIMANTAN - audah, abdul kadir (Archives of Business Research, 2019)
ABSTRACT This study aims to prove and analyze the influence of participation leadership, organizational culture, innovation to organizational capabilities and performance of cooperatives in the province of South Kalimantan. The population in this study were all Cooperatives that had implemented RAT in South Kalimantan Province as many as 660 Cooperatives, as many as 249 Cooperatives in the sample. The data used in this study are primary data sourced from the questionnaire. Data analysis and hypothesis testing in this study using the Structural Equation Model (SEM). The results of the hypothesis testing prove that participation leadership, organizational culture and innovation have a significant effect on organizational capacity in cooperatives in South Kalimantan. Participatory leadership has a significant effect on the performance of cooperatives in South Kalimantan. Organizational culture and innovation have no significant effect on the performance of cooperatives in cooperatives in South Kalimantan. Organizational ability has a significant effect on the performance of cooperatives in South Kalimantan. Keywords: Participation leadership, Organizational Culture, Innovation, Organizational Ability, Cooperative Performance